Death Receptor 3 (TNFRSF25) Increases Mineral Apposition by Osteoblasts and Region Specific New Bone Formation in the Axial Skeleton of Male DBA/1 Mice - Fraser L. Collins; Jessica O. Williams; Anja C. Bloom; Michael D. Stone; Ernest Choy; Eddie C. Y. Wang; Anwen S. Williams (Journal of Immunology Research)
Objectives. Genome wide association studies identified TNFSF member TNF-like protein 1A (TL1A, TNFSF15) as a potential modulator of ankylosing spondylitis (AS). TL1A is the only confirmed TNFSF ligand of death receptor 3 (DR3, TNFRSF25); however, its role in disease pathology is not characterised. We evaluated DR3’s role in controlling osteoblast- (OB-) dependent bone formation in vitro and in vivo. Methods. Osteoprogenitor cells and OB were cultured from male DR3-deficient (DR3ko) and wild-type (DR3wt) DBA/1 mice. DR3 and RANKL expression were tested by flow cytometry. Alkaline phosphatase and mineralization were quantified. Osteopontin, osteoprotegerin, and pro MMP-9 were measured by ELISA. A fluorescent probe (BoneTag) was used to measure in vivo mineralization in 10-month-old mice. Results. DR3 was expressed on osteoprogenitors and OB from DR3wt mice. Alkaline phosphatase, osteopontin, and mineral apposition were significantly elevated in DR3wt cultures. Levels of RANKL were comparable whilst osteoprotegerin was significantly increased in DR3wt cultures. In vivo incorporation of BoneTag was significantly lower in the thoracic vertebrae of 10-month-old DR3ko mice. Conclusions. These data identify new roles for DR3 in regulating OB-dependent bone mineral apposition. They potentially begin to explain the atypical pattern of new bone formation observed in the axial skeleton of grouped, aging DBA/1 mice.